Molecular description of the native nematodes, Heterorhabditis indica and Heterorhabditis megidis in Wasit province, Iraq - Nawar Jaber Alasdi; Muhammed Jubair Hanawi; Jawad Bulbul Al-Zaidawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study continued in Iraq / Wasit province during the period from October 2022 to October 2023. Samples were collected from different regions in this province (north, south, center, east, and west). The soil samples were 100 samples from these areas, from which soil samples were collected randomly from orchards (citrus and palm trees) and wheat fields. Entomopathogenic nematodes were isolated using insect white trap. Then, entomopathogenic nematodes were found in 60 samples, and entomopathogenic nematodes were identified based on a molecular approach. ITS rDNA genes were selected to characterize the isolated insect pathogenic nematodes. The isolates were contrasted with other nematode isolates and species in GenBank and described using nucleotide BLAST in NCBI. There were two distinct categories of isolates. These are Heterorhabditis indica (IRQ.1 (PP869212 Iraq/Wasit)), which was found to be, and Heterorhabditis megidis (IRQ.2 (PP869236) Iraq/Wasit), which was found to be the first isolate and diagnosis of Heterorhabditis. Sp in Iraq.